Reckless subjects, future capital? 'Youth' as an object of concern in international health organizations' discourse - Stadelmann, Felix; Kramer, Niklas; Pantzerhielm, Laura; Holzscheiter, Anna (Globalizations, 2025)
Contemporary international organizations (IOs) are routinely portrayed as being more accessible to a wide variety of actors than ever before. The recent hyper-institutionalization of youth in international politics testifies to this pluralization, at least quantitatively. This paper traces the historical emergence of youth as an object of concern among health IOs. Covering a period of over 50 years, we analyse semantic fields surrounding youth and find that young people have primarily been portrayed as society's future capital in development discourses or as a risk-prone group in the context of HIV/AIDS and reproductive health. Only since the beginning of the 21st century can we trace portrayals of youth that emphasize rights, inclusion and engagement in global health. Our study addresses an empirical research gap on youth in global health and prompts us to critically re-evaluate the optimistic liberal assessments that have marked International Relations (IR) theories on the 'opening-up' of IOs.